Chronic exposure to microcystin-leucine-arginine promoted proliferation of prostate epithelial cells resulting in benign prostatic hyperplasia. (November 2018) - Pan, Chun; Chen, Yabing; Xu, Tianchi; Wang, Jing; Li, Dongmei; Han, Xiaodong
Abstract: Microcystin-leucine-arginine (MC-LR), as a most common and deleterious variant among all structural analogues of Microcystins (MCs), can cause male reproductive dysfunction. However, its toxic effects on prostate in adult mice have not been invested in detail. In this study, we observed that MC-LR could enter prostate tissues and induce focal hyperplasia and prostate inflammation. Moreover, increased levels of prostate specific antigen (PSA) and prostate acid phosphatase (PAP) in serum of mice following chronic exposure to MC-LR were detected. We also examined increased expression of forkhead box protein M1 (FOXM1) and PSA in human prostate epithelial cells (RWPE-1) treated with MC-LR at low levels, and FOXM1 could regulate PSA expression. Furthermore, MC-LR also induced expression of CyclinD1 via FOXM1/Wnt/β-catenin signaling pathways in RWPE-1 cells, promoting proliferation of prostate epithelial cells, resulting in prostatic hyperplasia in vivo . As a foreign substance, MC-LR also induced immune reaction in RWPE-1 cells mediated by NF-κB pathway, promoting production of pro-inflammatory cytokines and chemokines. Collectively, these findings demonstrated that MC-LR may induce prostatic hyperplasia and prostatitis in mice following chronic low-dose exposure to MC-LR. This work may provide new perspectives in developing new diagnosis and treatment strategies for MC-LR-induced prostatic toxicity. Graphical abstract: Image 1 Highlights: MC-LR promotes proliferation of prostate epithelial cells in vivo . MC-LR induces increased levels of PSA, PAP and pro-inflammatory cytokines in serum and prostate tissues. FOXM1/Wnt/β-catenin pathway is involved in overexpression of CyclinD1 to promote proliferation of RWPE-1 cells. MC-LR induces immune reactions in prostate epithelial cells. Abstract : Chronic exposure to microcystin-LR induced benign prostatic hyperplasia.